Migracije nacionalizacije glasbe - Kovačič, Mojca (Dve domovini, 2023)
The paper discusses folk and folk-pop music from the perspective of the development of their symbolic meaning for the immediate and wider community. The migration of ascribed meanings and moral and aesthetic values from one era to another, from one community to another, or from one social class to another is the focus of the observation of these two musical genres, which link a number of dichotomies. If folk music played one of the most important nationally representative roles in the 20th century, in recent decades, folk-pop music has begun to play this role alongside folk music, as state policies have begun to accept it as part of their agenda, thus legitimizing it as a symbol of national representation.
Keywords: cultural nationalism; cultural policy; Kulturna politika; kulturni nacionalizem; nacionalna identiteta; national identity; Slovenian folk music; Slovenian folk-pop music; Slovenska ljudska glasba; Slovenska narodnozabavna glasba